BOOKKEEPING PRACTICES OF MICRO ENTERPRISES IN NORTHERN PHILIPPINES - DULIN, GIEHLITO CAMMAYO (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to determine the bookkeeping practices of micro enterprises in Northern Philippines. Specifically, it aimed to determine the demographic profile of the business owners of the microenterprises in terms of age, gender, educational attainment; the types of business activities engaged in; number of years in operation; bookkeeping practices and the extent of bookkeeping practices of microenterprises. The descriptive-qualitative research survey method was used in the study with 76 respondents chosen using the purposive sampling. Questionnaires and interviews were the instruments used in the data gathering. The data gathered were statistically analyzed using frequency counts, percentages, mean and weighted mean. Majority of the respondents are educated and in their middle-ages. The micro enterprises are female dominated and majority are engaged in the service business. The double-entry bookkeeping system and the accrual basis of accounting are used by the businesses. As to the extent of the practice of bookkeeping, all of the micro entrepreneurs must practice the daily, monthly, quarterly and annually bookkeeping practices while the weekly practices is moderately practiced.